THE EFFECT OF BRAND EXPERIENCE AND PERCEIVED VALUE ON BRAND LOYALTY MEDIATED BY BRAND TRUST - Pratiwi, Rima Sera; Salim, Ubud; Sunaryo, Sunaryo (Jurnal Aplikasi Manajemen, 2021)
This study aimed to investigate the direct effect of brand experience and the perceived value of customers on brand loyalty and the indirect effect through brand trust as mediating variable. This study used a questionnaire distributed to 130 loyal customers of Susu Nandhi Murni produced by KUD Batu. The sampling technique was purposive sampling, and the method of data analysis was Partial Least Square (PLS). The results demonstrated a positive and significant direct effect of brand experience and perceived value on brand loyalty. In addition, brand experience and perceived value also had a positive and significant effect on brand trust and brand trust on brand loyalty. Furthermore, the indirect effect through brand trust as mediating variable also revealed a positive and significant effect, both on the brand experience and perceived value. Finally, future studies are suggested to investigate other variables that were not discussed in this research, such as brand image and brand satisfaction.